Predictors of failure of retrograde approach for percutaneous intervention of coronary chronic total occlusion: A single-center experience - Jianying Ma (Cardiology Plus, 2019)
Objective: The aim of the study is to assess the predictors of failure of percutaneous coronary intervention (PCI) of chronic total occlusion (CTO) lesions using a retrograde approach. Methods: The present study retrospectively enrolled all 211 patients who underwent retrograde CTO PCI from January 2009 to December 2015 at Shanghai Institute of Cardiovascular Disease. Multivariate Cox regression analysis was used to assess potential predictors of retrograde CTO PCI failure including sex, vascular access site, sheath size, prior PCI, prior coronary artery bypass grafting, history of myocardial infarction, target vessel of CTO, J-CTO score, retrograde wire crossing collaterals, and reverse controlled antegrade and retrograde subintimal tracking (CART) use. Results: Of the 211 patients studied, retrograde CTO PCI was successful in 115 (54.5%) patients, and in an additional 46 (21.8%) with an antegrade approach after retrograde failure. For the 50 (23.7%) patients who failed both retrograde and antegrade approaches, the most common (50% [25/50]) reason was inability to cross collaterals with the retrograde wire. This group of patients had fewer instances of a prior PCI (P < 0.05). Retrograde CTO PCI failure rate was lower with increasing sheath size and with either radial-only or one radial and one femoral access versus femoral-only access (P < 0.05). A multivariate Cox regression analysis showed that the inability to cross collaterals with the retrograde wire (hazard ratio, 5.52 [95% confidence interval, 2.08–12.81];P < 0.001), no prior PCI (3.27 [1.24–8.58];P = 0.01), and no reverse CART use (4.19 [1.33–13.19];P = 0.03) were an independent predictors of retrograde CTO PCI failure. Conclusion: Independent predictors of retrograde CTO PCI failure were the inability to cross collaterals with the retrograde wire, no prior PCI, and no reverse CART use. Vascular access site and sheath size do not have effect on the success of the retrograde approach.